Concanavalin A Enhanced Proliferation and Osteogenic Differentiation of Dental Pulp Stem Cells - Suardita, Ketut; Arundina, Ira; Tedjosasongko, Udijanto; Yuliati, Anita; Peeters, Harry Huiz; Wijaksana, I Komang Evan; Surboyo, Meircurius Dwi Condro (European Journal of Dentistry, 2020)
Objective Dental pulp stem cells (DPSCs) can be used as a component in the formation of regenerative dentine during direct pulp capping therapy. Concanavalin A (ConA) is a type of lectin with a molecular weight of 26 kDa derived from the Canavalia ensiformis plant. Lectins possess strong proliferation and differentiation abilities in various animal cells including lymphocytes, osteoblasts, and chondrocytes. The aim of study was to determine the effect of ConA on the proliferation and osteogenic differentiation of DPSCs in vitro.Materials and Methods In this in vitro study, DPSCs were isolated from third molars before ConA induction was performed at concentrations of 5 and 10 μg/mL. The proliferation assay was determined by 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Osteogenic differentiation was determined by means of mineralization.Statistical Analysis Data were analyzed using analysis of variance and a Student’s t-test. The p-value was set at 0.05.Results The addition of 5 and 10 µg/mL of ConA to DPSCs can significantly increase the proliferation and osteogenic differentiation of DPSCs (p ≤0.05).Conclusion ConA can increase the proliferation and osteogenic differentiation of DPSCs.
Keywords: concanavalin A; dental pulp; differentiation; proliferation; stem cell